MEMAHAMI PERAN YESUS DAN ROH KUDUS DALAM INJIL LUKAS DENGAN BINGKAI PEMIKIRAN PIERRE FELIX BOURDIEU - Tumiwa, Krueger Kristanto (Tumou Tou, 2019)
This article aims to understand the role of the Holy Spirit and Jesus in Luke's Gospel using an interpretive approach that utilizes social science. This way of understanding is called an effort to understand the text using a social approach (utilizing social sciences). This article uses a descriptive analysis method by describing research results from various primary and secondary literature sources related to the topic. The Holy Spirit in Luke's Gospel has an important role in the work of Jesus' ministry. The writer of the Gospel of Luke does pay special attention to the Holy Spirit in his writings. This article wants to examine how the position or role of the Holy Spirit and Jesus themselves in social practice uses the thoughts of Pierre Felix Bourdieu. Some important things from Bourdieu such as habitus, agency, capital, and social practice become the emphasis in this article.